'Synergy', 'energy' and 'symbol' in Pavel Florensky and Palamism. Issue 2 (May 2021) - Biryukov, Dmitry
Abstract: This article is a study of Pavel Florensky's philosophy of symbol in the context of his discovery of Palamism in the 1910s, when Florensky started to speak of symbol using Palamite language. It proposes a fundamental difference between Florensky's and Palamas' teachings on symbol: Palamas views a natural symbol as the energy of an essence, while for Florensky symbol is the essence itself, the energy of which synergises with the energies of other essence. In this context the prehistory of the concept of synergy in Florensky is studied, leading to the identification of a further difference in the ontologies of Florensky and Palamas: while Florensky's 'essence-energy' has the property of necessary correlation with the 'other', following the tendencies of the philosophy of that epoch, in Palamas 'energy' does not presuppose any necessary correlation with the 'other'. The author connects this difference in ontologies between the two thinkers with their respective teachings on symbol.